User acceptance of Health Information Technology (HIT) in developing countries: a conceptual model - Ahlan, Abdul Rahman; Ahmad, Barroon Isma'eel (Elsevier Ltd., 2014)
Health Information Technology (HIT) has the potential to improve the quality, efficiency, outcomes, patient safety and reduce the cost of healthcare. But HIT systems are not widely available, and even if available are not properly utilized. This paper reviewed some available HIT systems in order to have an idea on their availability. Also works on acceptance of HIT systems were reviewed so as to understand the level of research done in the area. The problems identified from this work include lack of availability of these systems especially in developing countries, insufficient works on user acceptance of HIT systems, etc. These limitations can be overcome when researchers study the factors that will affect the user acceptance of these systems, and then consider the factors while developing the systems.